Marketing Politik Program Makan Gratis sebagai Alat Kampanye: Pendekatan Komunikasi Politik dalam Pilpres 2024 - Harmonis, Harmonis; Faradila, Anez; Amanda, Fajrial Rizqi; Nizami, Ghiyats (TSAQOFAH, 2025)
The “free meal” program promoted by Prabowo Subianto and Gibran Rakabuming Raka during the 2024 Presidential Election garnered significant public and media attention as a populist strategy and a form of political communication aimed at reaching low-income groups. This study aims to analyze the use of the program as a campaign tool across various communication channels, including social media, political advertisements, and direct public engagement. Using a critical discourse analysis approach, the study explores how the “free meal” program was constructed to shape the candidates’ image as leaders who are empathetic and close to the common people. The findings reveal that the strategy was effective in generating positive public opinion, despite ongoing criticism concerning its implementation and long-term sustainability. The study highlights the central role of political communication in shaping voter perceptions and underscores the growing presence of populist practices within Indonesia’s digital campaign landscape.